Determination of porcine gelatin in edible bird's nest by competitive indirect ELISA based on anti-peptide polyclonal antibody - Tukiran, Nur Azira; Ismail, Amin; Mustafa, Shuhaimi; Hamid, Muhajir (Elsevier, 2016)
Competitive indirect enzyme-linked immunosorbent assay (ELISA) was developed for rapid detection of porcine gelatin in edible bird's nest (EBN). Three ELISAs were developed by using polyclonal rabbit antibodies against porcine species-specific amino acid sequences of collagen α2 (I) chain (pAb1 and pAb2) and α1 (I) chain (pAb3). The limit of detection (IC15) of the three ELISAs was 0.033, 0.082 and 0.052 μg/mL respectively. The median inhibitory concentration (IC50) of pAb1, pAb2 and pAb3 was 0.265, 0.394 and 0.228 μg/mL respectively, as well as able to recognise porcine and bovine gelatins. pAb1 showed slight cross-reactivity with cave nest and egg white, while pAb2 exhibited slight cross-reactivity with blood cave nest and egg white. No cross-reactivity was observed with EBNs and egg white for pAb3. The recoveries of porcine gelatin spiked EBNs were in the range of 62.8–125.4% with intra- and inter-day coefficient of variants (CVs) of 2.9–5.4% and 4.7–9.6% respectively when using pAb3. Taking into account all abovementioned factors, pAb3 appeared sufficient for EBN authentication.